Do direito à educação : o núcleo de atendimento às pessoas com necessidades específicas e a inclusão escolar no IFES - Perinni, Sanandreia Torezani (2017)
Considering education as a subjective public social right, the objective of this study was to investigate whether the actions developed by the Napne of the campus Itapina and Santa Teresa of the Instituto Federal do Espírito Santo can guarantee the conditions of access, permanence, participation and learning of students with needs in profissional education integrated with secondary education. A qualitative research approach was used, from the perspective of the case study, which focused the Napne of the campus Itapina and Santa Teresa through the participation of the 16 members, but also analyzed in general the Ifes, through the participation of members of the Pró-Reitoria de Ensino (03), Coordinators of the Napnes in the Ifes (12), students attended by Napnes of Itapina and Santa Teresa (08). As procedures for producing the data, I used documentary analysis, semi-structured interviews, questionnaires and focus groups. In terms of results, in the eyes of the students, the actions of the Napne have made possible the access and the learning, because they seek to understand the demands of the students and to supply them. In the eyes of Napne staff and coordinators, many have been the challenges and barriers to building the process of inclusion of students with NEE in the Ifes and highlight as major obstacles the absence of budget availability and specific human resources for the Napne. It was also pointed out the need to expand the publicity of the Napne in the institution to constitute an identity of this in the institution. Through documentary analysis, it was possible to perceive that the institution has constructed the legislation assuring some actions and establishing some protocols of action. However, there is also an indication that an institutional practice needs to be elaborated, as well as protocols to act in harmony with the Napnes' performance in the institution. From the reports of the members of the Napne there are some institutional aspects that need to be broken such as the resistance to inclusive education, the disarticulation between the Napne and the sectors of the institution and the internal political differences between the managers. Among the facilitating institutional aspects, it can be observed in the documents that there are guiding principles of inclusive education in the Statute of the Federal Institutes (Ifs) and in the institutional documents. In order for Napne's actions to foster the inclusion of subjects with NEE in the network, some more specific actions are required: the acquisition of permanent material / consumption and new technologies, the hiring of a specialized professional, the valuation of the Inclusive Policy minimizing attitudinal resistance and the regulation of inclusive education in the institution. Despite the challenges, it is possible to affirm that the Napne's actions and the actions developed by it have harmony with the policy proposed by TecNep, in addition to concretizing in practice the culture theory of "education for coexistence", in a professional education institution and technological -Ifes and this has sought to adapt to the new demands given by the inclusion process.